Fate of buturon-14C in soil during seven seasons of exposure under outdoor conditions - Constenla Umaña, Manuel Arturo (1984)
Buturon (ring 14C) was applied to wheat and soil in two successive years (3 kg/ha each year) at outdoor conditions. Residual radioactive substances in the upper soil layer (0-10-cm depth) were measured 1.5, 2.5, 3.5, 6.0, and 6.5 years after the first treatment. The decline of total radiocarbon was a two-stage process. Mass balance studies were conducted 1.5, 2.5, and 6.5 years after the first treatment; total recoveries were 83, 47, and 27 %, respectively, of the applied radioactivity. Extractability of residues with cold chloroform was 20-30% of total residues. Whereas the chloroform-soluble conversion products identified after the first growing period mostly resulted from alterations within the side chain of buturon, after seven seasons only hydroxylated and/or methoxylated derivatives of 4-chloroaniline could be detected.